PENINGKATAN PRODUKTIVITAS DAN KUALITAS PRODUK MELALUI PENERAPAN TEKNOLOGI TEPAT GUNA PADA USAHA PENGEMBANG EKONOMI LOKAL DI KOTA MOJOKERTO PROPINSI JAWA TIMUR - Nekky Rahmiyati; Muslimin Abdul Rahim (JPM17: Jurnal Pengabdian Masyarakat, 2015)
One of the goals of the National Development is community empowerment programs.  Mojokerto Government has made the empowerment program, known as the Local Economic Development Women's Empowerment (P3EL).  This program was to empower women to increase their  income. They came from the P3EL group who produced cakes / snacks / local bakery. The objectives of this program: 1) supplying proofer tool, a tool to expand the dough and biscuit maker tool of 6 (six) furnaces. 2) Mentoring the ability to manage the business, making media marketing, in term of banner. The applied method consisted of identifying the crucial issues to settle immediately including the energy efficient, time and cost; conducting training and assisting on business development management and simple bookkeeping; conducting training  on marketing techniques and strategies; creating marketing media in the form of banners. The results and implications were  2 proofer machine, 1 mold tool 6 furnaces and banner have been handed over to the SMEs; business management training. The implication of the program was that there was an increase in productivity of SMEs and understanding and having knowledge in business management and business management.Keyword: Empowerment, Women, Improvement, Income, Family